2010
DOI: 10.1177/0022034510385459
|View full text |Cite
|
Sign up to set email alerts
|

Oral Epithelial Cells are Activated via TRP Channels

Abstract: Transient receptor potential (TRP) ion channels are critical contributors to the perception of various environmental stimuli. Although the oral cavity is the access point for various food types, the expression of TRP channels in oral mucosa remains unknown. We hypothesized that the oral epithelium itself may participate in sensing thermal, mechanical, and chemical conditions. The expression profiles of TRP channels exhibited regional differences among the buccal, palatal, and tongue epithelia. Changes in eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…In the present study, we confirmed TRPV4 protein expression by in situ hybridization, Western blotting, immunohistochemistry, and immunocytochemistry, in accord with our previous reports on TRPV4 mRNA expression in rats and mice . Antibody specificity against TRP channels has challenged many researchers, including us.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we confirmed TRPV4 protein expression by in situ hybridization, Western blotting, immunohistochemistry, and immunocytochemistry, in accord with our previous reports on TRPV4 mRNA expression in rats and mice . Antibody specificity against TRP channels has challenged many researchers, including us.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier publications had suggested a role for the direct activation of oral epithelial cells by polyphenols (Wang et al . ; Kurogi et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Expression patterns of TRPV1, 3, and 4 have previously been reported in normal tongue, buccal mucosa, and palate tissue of rats [19], while TRPV3 is reported as involved in healing mucosal injury in rat palatal mucosa [20]. In humans, quantitative expression analysis of TRPV1 has been reported in the lingual mucosa and oral squamous cell carcinoma (SCC) [16, 21].…”
Section: Introductionmentioning
confidence: 99%